Improving Student Learning Outcomes VIII. An SMP Negeri 3 Kendari on the Material of Two-Variable Linear Equation Systems Through Learning Models Cooperative Type Think Pair Share - Marthinus Buntu (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This study aimed to improve student learning outcomes on the material of a two-variable linear equation system by applying the Think Pair Share type of cooperative learning model—classroom action research conducted in class VIII.A of SMP Negeri 3 Kendari. The research implementation phase involves planning, observation, action, and reflection. The study was carried out in two cycles because, in the first cycle of the 12 aspects of the teacher's activities, the observations were 83.3% for ten factors with excellent (SB) and sound (B) criteria. From 12 elements of the action, nine aspects, or 75%, obtained the requirements of perfect (SB) and sound (B) for student activities. Based on the analysis of student learning outcomes acquired from 36 students who were subjected to action, it turned out that only 23 students, or 63.9%, had obtained a score of 65. Based on the analysis results in the first cycle, it was necessary to carry out a follow-up cycle (cycle II). The results of observations in cycle II of all aspects of teacher activities obtained observations of 100% for 12 elements with perfect criteria (SB) and good (B). In comparison, student activities received statements also of 100% for 12 pieces with perfect bars (SB). ) and good (B). Similarly, student learning outcomes in the second cycle of 36 students, there are 32 students or 88.9% who have scored 65 and above, so the expected absorption has been achieved based on the predetermined completeness criteria. Based on the results of the analysis above, by using the Think Pair Share type cooperative learning model, the learning outcomes of VIII.A SMP Negeri 3 Kendari student on the material of a two-variable linear equation system can be improved.